The frontier club : popular westerns and cultural power, 1880-1924 - Bold, Christine, 1955- (Oxford University Press, 2013)
'The Frontier Club' is Christine Bold's name for the network of eastern aristocrats who created the western as we now most commonly know it. At the turn of the twentieth century, they yoked this most popular formula to their own elite causes - from big-game hunting to conservation, immigration restriction to Jim Crow segregation - and aligned themselves with cattle kings and 'quality' publishers. This book tells the story of that cultural sleight-of-hand.